Laser monitors for high speed imaging of materials modification and production - Trigub M. V. Maksim Viktorovich; Platonov V. V. Vladimir; Evtushenko G. S. Gennady Sergeevich; Osipov V. V. Vladimir Vasiljevich; Evtushenko T. G. Tatjyana Gennadjevna (2017, 2017)
Title screen